Teacher Strategies in Creating Fun Learning for Class IV Students of Madrasah Ibtidaiyah - Abidin, Achmad Anwar; Ismawati, Ismawati; Suyadi, Suyadi (MODELING: Jurnal Program Studi PGMI, 2024)
This article is the result of field research, qualitative with a study approach on class IV students of Madrasah Ibtidaiyah Al Fithrah Balongpanggang Gresik. The data was collected from interviews, observations, and document tracing. The results show that: the teacher's strategy in creating fun learning is to involve children directly in teaching, emphasizing increasing learning motivation, using interesting and varied learning methods, using play strategies while learning or ice breaking.